Banks as Buyers of Last Resort for Government Bonds? - Daniel Gros (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2017)
A key remaining issue for the completion of the Banking Union is the concentrated exposure of banks in many countries to their own sovereign. This paper examines the belief that banks should be allowed to buy large amounts of their own sovereign so that they can stabilise the market in a crisis and argues that it is mistaken for two reasons. In the first instance, banks are only intermediaries for private savings, and secondly, banks have a higher cost of funding than do their sovereign. The overall conclusion is that governments should make it more attractive for households (and other real money investors) to hold government debt directly. One of the key remaining key issues for the completion of the Banking Union is the concentrated exposure of banks in many countries to their own sovereign. A number of contributions have argued that banks should be discouraged from holding too much government debt and in particular should be discouraged from holding too much debt of their own government (Andritzky et al., 2016, ASC, 2015 and Korte & Steffan, 2014). The key counter-argument is that banks should be allowed to buy large amounts of their own sovereign because in this way they can stabilise the market in a crisis.~ Visco (2015) argues: … tight concentration limits could create substantive difficulties in "crisis" times. They could be particularly disruptive for banks' ability to act as shock absorbers in the event of sovereign stress…. This argument is mistaken, however. As explained below, there are two reasons why the act of a bank buying the bonds of its own national government does not have a large positive impact on bond prices.
Keywords: 330